Analysis of full length transcriptome and resistance characteristics of Atraphaxis bracteata under drought - Cai He; Wei Liu; Min Jin; Yi Li; Yuan Wu; Lishan Shan; Peifang Chong; Meiying Wei; Fang Hu; Yuan Liu; Chaoqun Li; Qinde Zhang (Scientific Reports)
Abstract Drought is one of the main environmental factors affecting plant survival and growth. Atraphaxis bracteata is a common desert plant mainly utilized in afforestation and desertification control. This study analyzed the morphological, physiological and molecular regulatory characteristics of different organs of A. bracteata under drought stress. The results showed that with the intensification of drought stress, the height, root length and leaf area of A. bracteata seedlings decreased, while the content of osmotic substances and antioxidant enzyme activity increased. Furthermore, a total of 63 907 non-redundant transcript sequences, of which 55 574 transcripts were annotated, 248 178 FLNC sequences, 107 112 high-quality consistent sequences and 291 314 CCSs were obtained from Iso-Seq. Meanwhile, a total of 2 039 AS events, 22 919 SSR, 40 404 CDS and 5 902 lncRNA were also obtained. The RNA-Seq analysis results revealed that a total of 2 821, 3 907 and 5 532 DETs were identified from roots, stems and leaves, respectively, and which had significantly enrichment in “circadian rhythm-plant” and “starch and sucrose metabolism” pathway. These results would be great significance for further research on the stress resistance of A. bracteata and these DETs function.